The legal framework for European cervical cancer screening programmes. (27th September 2018) - Májek, Ondřej; Anttila, Ahti; Arbyn, Marc; van Veen, Evert-Ben; Engesæter, Birgit; Lönnberg, Stefan
Abstract: Background: A comprehensive legal framework needs to be developed to run the health services and to regulate the information systems required to manage and to ensure the quality of cancer screening programmes. The aim of our study was to document and to compare the status of legal basis for cervical screening registration in European countries. Methods: An electronic questionnaire including questions on governance, decision-making structures and legal framework was developed. The primary responses were collected by September 2016. Results: We sent the questionnaire to representatives of 35 European countries (28 countries of the EU, with the United Kingdom included as 4 countries; 4 EFTA member countries: Iceland, Liechtenstein, Norway, and Switzerland); responses were collected from 33 countries. The legal framework makes it possible to personally invite individuals in 29 countries (88%). Systematic screening registration in an electronic registry is legally enshrined in 23 countries (70%). Individual linkage of records between screening and cancer registries is allowed in 19 of those countries. Linkage studies involving cancer and screening registries have been conducted in 15 countries. Conclusion: Although the majority of EU/EFTA countries have implemented population-based screening, only half of them have successfully performed record linkage studies, which are nevertheless a key recommendation for quality assurance of the entire screening process. The European legislation is open to the possibility of using health data for these purposes; however, member states themselves must recognize the public interest to create a legal basis, which would enable all the necessary functions for high-quality cancer screening programmes.